Pandongani Boru Tradition in Padang Lawas Muslim Community Wedding from the Perspective of `Urf - Paet Hasibuan; Sukiati Sukiati (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2023)
Pandongani Boru is a tradition of the Padang Lawas community in which a girl accompanies the bride when she is brought to the martua's house directly after the wedding party is over. If the Pandongani Boru tradition is not carried out, the marriage of the bride and groom is considered invalid by traditional leaders and the community is prohibited from assisting in the implementation of the wedding party. This tradition is not regulated in Islamic law, but to this day the community still implements and dares not abandon this Pandongani Boru tradition. This study aims to find out the views of the Padang Lawas Muslim community towards the Pandongani Boru tradition. In addition, this study also aims to find out the reasons why the people of Padang Lawas still maintain the Pandongani Boru tradition in their marriage ceremony. The next objective of this study is to find out the Pandongani Boru tradition in the Padang Lawas Muslim community based on the `Urf review. By using qualitative research methods, data was collected by interviewing the participants. This study found that the results of the research found by researchers that the Pandongani Boru tradition is a tradition that has been carried out by the community from the past until now. The reason they carry out pandongani is because this tradition does not conflict with Islamic law. And to maintain good customary kinship relations. This research concludes that traditions accepted through the perspective of `Urf can be adopted by Islamic law. And that customary law and Islamic law still coexist harmoniously in Indonesian society. This research contributes to the strengthening of theories of the intersection of Islamic law and customary law in Indonesia.